2017
DOI: 10.1021/acs.jafc.7b01752
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Rapid Method for Screening Heat Stress Tolerance Using Three Korean Wheat (Triticum aestivum L.) Cultivars

Abstract: Thermotolerance in plants is a topic of concern given the current trends in global warming. Here, we aimed to develop a rapid and reproducible screening method for selection of heat stress-tolerant wheat varieties to expedite the breeding process. We tested the robustness of the screen in three Korean wheat cultivars, "BackJung", "KeumKang", and "ChoKyeong". We showed that 4-day-old seedlings of "KeumKang" had the highest survival rates after a 45 °C treatment for 20 h. Moreover, the ability to retain chloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Three-week-old plants were challenged with 0 or 300 mM NaCl for 8 days, and the rosette leaves were collected and used. The assay was performed according to the previous study (Truong et al, 2017). Samples were homogenized using 0.1% (w/v) trichloroacetic acid (TCA) and centrifuged at 12,000 rpm, 4 • C for 15 min.…”
Section: Lipid Peroxidation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Three-week-old plants were challenged with 0 or 300 mM NaCl for 8 days, and the rosette leaves were collected and used. The assay was performed according to the previous study (Truong et al, 2017). Samples were homogenized using 0.1% (w/v) trichloroacetic acid (TCA) and centrifuged at 12,000 rpm, 4 • C for 15 min.…”
Section: Lipid Peroxidation Assaymentioning
confidence: 99%
“…Rosette leaves were sampled and used for this assay. The assay was performed according to a previous study (Truong et al, 2017). Samples were homogenized in 3% aqueous sulfosalicylic acid and the supernatant was collected after centrifugation at 12,000 rpm for 10 min.…”
Section: Proline Contentmentioning
confidence: 99%
“…Proline accumulation, which is involved in cellular osmoregulation and protection of cellular structures against increased temperatures by cell water balance conservation and stabilization of biological membranes, is an important adaptive response in crops exposed to high temperatures (Wahid et al 2007, Bita andGerats 2013). Accumulation of proline has been reported to increase in response to heat stress in wheat genotypes (Dhyani et al 2013, Truong et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies related to higher or lower temperature treatments in in vitro plants had been conducted. Truong et al, (2017) reported that treatments of high temperature at 45 o C at 4day-old seedling of several wheat cultivars for 20 h had the highest survival rates, which means that those cultivars might be candidates of heat tolerant cultivars. An and Zhang (2012) also reported that different low temperaturetreated cassava apical shoots for 0, 4 and 9 h had different performances and genetic profiling changes, which means they responded to cold stress.…”
Section: Discussionmentioning
confidence: 99%